Bycatch of sharks, marine mammals and seabirds in Indonesian Tuna Longline Fishery - IMAM MUSTHOFA ZAINUDIN; MUFTI PETALA PATRIA; PRIYANTO RAHARDJO; YASMAN YASMAN; DWI ARIYOGA GAUTAMA; WAHYU TEGUH PRAWIRA (Biodiversitas Journal of Biological Diversity, 2017)
Zainudin IM, Patria MP, Rahardjo P, Yasman, Gautama DA, Prawira WT. 2017. Bycatch of sharks, marine mammals and seabirds in Indonesian Tuna Longline Fishery. Biodiversitas 18: 1179-1189. Bycatch in longline fishery is recorded to be one of the major factors defining the declined populations of endangered marine species worldwide. This research aimed to identify bycatch level of sharks, marine mammals and seabirds as well as to pinpoint the mitigation options in Indonesian tuna longline fishery. In this study, a total of 8,564,858 hooks were observed from 5,622 gear settings in Indonesian tuna longline fishery based in two major fishing ports, namely Bitung Fishing Port-North Sulawesi and Benoa Port-Bali from May 2006 to June 2014. The results suggest that the best hook rate per thousand hooks in Indonesian tuna longline fisheries for shark bycatch was 0.2446, followed by 0.0030 for seabird bycatch, 0.0021 for dolphin bycatch and 0.0009 for whale bycatch. Seabirds largely acquired in the dead condition while the other species were found still alive (sharks and marine mammals). Bycatch of seabirds only occured in the vessels based in Benoa Bali, and the correlation value (R2) of sharks and seabirds caught at night time was low while for marine mammals was very strong. Deep setting system of fishing gears and night setting also proved to be more effective to reduce bycatch of those critical marine species.